Identification and Characterization of Atmospheric Nickel-Containing Particles in Guangzhou After the Implementation of the Clean Fuel Policy - Zaihua Wang; Xuanxiao Chen; Cheng Wu; Hong Ju; Zhong Fu; Xin Xiong; Ting Qiu; Yuchen Lu; Junjie He; Yaxi Liu; Haining Wu; Chunlei Cheng; et al. (Toxics)
Nickel, as a toxic trace element in fine particulate matter (PM2.5), has detrimental effects on both air quality and human health. Based on measurements from 2020 to 2021 using a single-particle aerosol mass spectrometer (SPAMS), this study investigates the properties of nickel-containing particles (NCPs) in Guangzhou. The composition, sources, and temporal trends of NCPs were evaluated and the impact of the clean ship fuel policy introduced in 2020 was also examined. The key findings include: (1) Nickel particles account for 0.08% number fraction of PM2.5, which is consistent with previously reported mass fraction in PM2.5. (2) Three distinct types of NCPs were identified, including Ni-fresh, Ni-aged, and Ni-ash. Each type exhibits unique characteristics in size distribution, wind direction dependence, sources, and temporal variations. Ni-fresh particles originate from shipping emissions in the Huangpu Port area 2 km away and are the major contributors to fine nickel particles in the region. (3) Ni-aged and Ni-ash particles, which carry secondary components, tend to be larger (>500 nm) and are representative of regional or background nickel particles. (4) The implementation of the clean ship fuel policy has effectively reduced the number concentrations of NCPs and is beneficial to regional and local air quality.